Social and Psychological Nature and Essence Public Opinion - Shamsiddinova, E. (European Journal of Life Safety and Stability (2660-9630), 2021)
The variety of points of view about the nature and purpose of the public opinion is largely due to the fact that in history and modernity there is not a single a prominent scientist (thinker), political and statesman who did not give his characteristics to public opinion. Analysis, description of individual sides of this phenomenon are found in religious teachings and mythological legends, Indian, Chinese, ancient Greek philosophy, later scientific research, as well as in the works of modern scientists, incl. philosophers, sociologists, political scientists and of course psychologists.